Desain Underwater Rotor Untuk Memanfaatkan Laju Aliran Sungai Sebagai Pembangkit Listrik Tenaga Air - rendi rendi; Budi Hatradi; Muhammad Irfansyah; Puteri Puteri (Jurnal Engine: Energi, Manufaktur, dan Material, 2021)
This study aims to design an underwater rotor to utilize the flow rate of the river as a hydroelectric power plant. In this study, an underwater rotor design model will be made with three variations in the number of blades, namely three, six, nine blades. The test parameter observed in this study is the turbine performance through the value of the power coefficient (cp) and the moment coefficient (cm). The method used in this research is an experimental method, namely by making a turbine model with a laboratory scale. The results show that the underwater rotor designed with aspect ratio = 2.0, overlap ratio = 0, end-plate diameter = 1.1d then the barrier plate design with L/D ratio = 1.2 60º provides the highest power coefficient and moment coefficient, namely respectively 0.15 and 0.27 in the design with the number of blades 3 (three)